Bodyweight and body condition score in rabbits on four different feeding regimes. (21st December 2014) - Prebble, J. L.; Shaw, D. J.; Meredith, A. L.
<x xml:space="preserve">Abstract</x> OBJECTIVES The aim of this study was to assess the effects of four diet regimes (extruded diet with ad lib hay, muesli with ad lib hay, ad lib hay only, ad lib muesli only) on bodyweight and body condition score in rabbits. METHODS Thirty‐two Dutch rabbits were studied over 9 months. Bodyweight and body condition score were recorded weekly. RESULTS All groups gained weight with age, but relative to the ad lib hay only group (mean, 1 · 77 ± 0 · 13 kg), after 9 months rabbits in the ad lib muesli only group were 146% heavier (2 · 59 ± 0 · 32 kg); extruded diet with ad lib hay group 125% heavier (2 · 21 ± 0 · 10 kg); and muesli with ad lib hay group 123% heavier (2 · 18 ± 0 · 13 kg). Median body condition score of the ad lib muesli only group was obese (4 · 5) and was higher than that in both the extruded diet with ad lib hay and muesli with ad lib hay (median = 3 · 5) groups (P < 0 · 001). Both the extruded diet with ad lib hay and muesli with ad lib hay groups had above‐ideal body condition score despite having bodyweights within the breed standard range. The ad lib hay only group had a median body condition score of 3 (ideal). There was an overall positive correlation between body condition score and weight (qs = 0 · 814, P < 0 · 001). CLINICAL SIGNIFICANCE The feeding of muesli without hay should be avoided, to prevent obesity.